2020
DOI: 10.1016/j.biopsych.2020.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Hippocampal Afferents to Nucleus Accumbens Encode Both Latent Vulnerability and Stress-Induced Susceptibility

Abstract: BACKGROUND: Stress is a major risk factor for depression, but not everyone responds to stress in the same way. Identifying why certain individuals are more susceptible is essential for targeted treatment and prevention. In rodents, nucleus accumbens (NAc) afferents from the ventral hippocampus (vHIP) are implicated in stress-induced susceptibility, but little is known about how this pathway might encode future vulnerability or specific behavioral phenotypes. METHODS: We used fiber photometry to record in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 51 publications
2
52
0
Order By: Relevance
“…This result provides electrophysiological evidence for early life adversity influencing glutamate transmission within the NAcC and complements previous work demonstrating that maternal separation stress leads to decreased GluA2 AMPA subunit expression in the NAc of males but not of females (29). Of note, many other studies have demonstrated stress-induced increases in glutamate transmission within the NAc, but those studies focused on recordings in the NAc shell and primarily examined the influence of stress exposure during adulthood (30)(31)(32).…”
Section: Lbn Decreases Self-administration Of a Low Dose Of Morphine Insupporting
confidence: 83%
“…This result provides electrophysiological evidence for early life adversity influencing glutamate transmission within the NAcC and complements previous work demonstrating that maternal separation stress leads to decreased GluA2 AMPA subunit expression in the NAc of males but not of females (29). Of note, many other studies have demonstrated stress-induced increases in glutamate transmission within the NAc, but those studies focused on recordings in the NAc shell and primarily examined the influence of stress exposure during adulthood (30)(31)(32).…”
Section: Lbn Decreases Self-administration Of a Low Dose Of Morphine Insupporting
confidence: 83%
“…Although pharmacological inactivation of the VTA completely abolishes the 4 Hz NAc oscillation, other circuit elements, including excitatory inputs or local interneurons, may modulate the amplitude of 4 Hz NAc oscillations 44 . For example, there is evidence that vHPC projections to the NAc are activated by aversive stimuli and mediate stress susceptibility 15,47,48 . Future studies will determine how other inputs and local microcircuitry contribute to the 4 Hz NAc oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…Future work dissecting subregion-and axisspecific hippocampal maturation in both sexes is necessary to identify possible mechanisms underlying the emergence of sex differences in hippocampal-dependent behavior. Finally, recent research tying adult sex-specific stress susceptibility to changes in the ventral hippocampus-nucleus accumbens circuit (Muir et al, 2020;Williams et al, 2020) further asserts a pressing need to expand these efforts toward the identification of sex-and circuit-specific maturation trajectories within sensitive circuits, as a means to search for potential contributions to both stress sensitivity and behavioral emergence in males and females.…”
Section: Summary and Implications Of Sex Differences In The Developinmentioning
confidence: 99%